Persistent SARS-CoV-2 RNA Positive in Feces but Negative in Breastmilk: A Case Report of COVID-19 in a Breastfeeding Patient - Chu, Huikuan; Li, Jing; Yan, Jingjing; Bai, Tai; Schnabl, Bernd; Zou, Li; Yang, Ling; Hou, Xiaohua (Frontiers in Medicine, 2020)
COVID-19 is a pandemic infectious disease. Whether SARS-CoV-2 RNA exists in breastmilk is unknown. Here we firstly report a breastfeeding woman with COVID-19 presenting with gastrointestinal symptoms and persistent SARS-CoV-2 RNA positivity in both her oropharyngeal swabs and faeces, but negativity in her breastmilk. After appearance of serum SARS-CoV-2-IgG, she began to bottle feed her baby with breastmilk without transmission. This report facilitates understanding of breastfeeding-related risks in COVID-19.